Land Cover Modeling in 2034 in Waiheru Watershed, Ambon City, Indonesia Using CA-Markov - Rakuasa, Heinrich; Khromykh, Vadim (Politeknik Negeri Batam, 2025)
The increasing demand for land due to population growth and community activities in Ambon City certainly has an impact on land cover changes in the Waiheru Watershed. Therefore, it is important to model future land cover as a sustainable environmental planning material. This study aims to analyze land cover changes in 2014, 2019, 2024 and model land cover in 2034 with the Cellular Automata Markov Chain (CA-Markov) approach. This method integrates historical land cover data and factors driving land use change, elevation, slope, distance from road, distance from river, population, distance from point of interst. The results show a trend of conversion of mixed agricultural land into residential areas, which certainly has the potential to exacerbate ecosystem vulnerability in the Waiheru watershed. Settlement land cover continues to increase in area, namely 68.78 ha in 2014, 77.73 ha in 2019, 96.72 ha in 2024 and the modeling results in 2034 show that settlement land has an area of 138.65 ha, this is in contrast to the forest area which has decreased due to the expansion of population settlements.These findings are expected to provide insights for policy makers and urban planners in formulating sustainable land management strategies, as well as maintaining a balance between development needs and environmental conservation in the Waiheru watershed.